Comparative Perspectives on Oxytocin and Vasopressin Receptor Research in Rodents and Primates: Translational Implications. (25th April 2016) - Freeman, Sara M.; Young, Larry J.
Abstract : In the last several decades, sophisticated experimental techniques have been used to determine the neurobiology of the oxytocin and vasopressin systems in rodents. Using a suite of methodologies, including electrophysiology, site‐specific selective pharmacology, receptor autoradiography, in vivo microdialysis, and genetic and optogenetic manipulations, we have gained unprecedented knowledge about how these neuropeptides engage neural circuits to regulate behaviour, particularly social behaviour. Based on this foundation of information from rodent studies, we have started generating new hypotheses and frameworks about how the oxytocin and vasopressin systems could be acting in humans to influence social cognition. However, despite the recent inundation of publications using intranasal oxytocin in humans, we still know very little about the neurophysiology of the oxytocin system in primates more broadly. Furthermore, the design and analysis of these human studies have remained largely uninformed of the potential neurobiological mechanisms underlying their findings. Although the methods available for studying the oxytocin and vasopressin systems in humans are incredibly limited as a result of practical and ethical considerations, there is great potential to fill the gaps in our knowledge by developing better nonhuman primate models of social functioning. Behavioural pharmacology and receptor autoradiography have been used to study the oxytocin and vasopressin systems in nonhuman primates, and there is now great potential to broaden our understanding of the neurobiology of these systems. In this review, we discuss comparative findings in receptor distributions in rodents and primates, with perspectives on the functionality of conserved regions of expression in these distinct mammalian clades. We also identify specific ways that established technologies can be used to answer basic research questions in primates. Finally, we highlight areas of future research in nonhuman primates that are experimentally poised to yield critical insights into the anatomy, physiology and behavioural effects of the oxytocin system, given its remarkable translational potential.